A shared neural basis underlying psychiatric comorbidity - Xie, Chao; Xiang, Shitong; Shen, Chun; Peng, Xuerui; Kang, Jujiao; Li, Yuzhu; Cheng, Wei; He, Shiqi; Bobou, Marina; Broulidakis, M. John; van Noort, Betteke Maria; Zhang, Zuo; et al. (Nature medicine, 2023)
Recent studies proposed a general psychopathology factor underlying common comorbidities among psychiatric disorders. However, its neurobiological mechanisms and generalizability remain elusive. In this study, we used a large longitudinal neuroimaging cohort from adolescence to young adulthood (IMAGEN) to define a neuropsychopathological (NP) factor across externalizing and internalizing symptoms using multitask connectomes. We demonstrate that this NP factor might represent a unified, genetically determined, delayed development of the prefrontal cortex that further leads to poor executive function. We also show this NP factor to be reproducible in multiple developmental periods, from preadolescence to early adulthood, and generalizable to the resting-state connectome and clinical samples (the ADHD-200 Sample and the STRATIFY & ESTRA Project). In conclusion, we identify a reproducible and general neural basis underlying symptoms of multiple mental health disorders, bridging multidimensional evidence from behavioral, neuroimaging and genetic substrates. These findings may help to develop new therapeutic interventions for psychiatric comorbidities.
Online veröffentlicht: 24. April 2023
Gesehen am 14.10.2024